Needle stick injury among health care workers in tertiary care setting in Peshawar - Ahmad, Shahzad; Khan, Mohammad Sajjad Ali; Ali, Tajdar; Ahmad, Wiqar; Shehzad, Kasif; Ilyas, Muhammad (International Journal of Pathology, 2026)
Background: Needle-stick injuries (NSIs) represent a significant occupational risk for healthcare workers and increase the likelihood of exposure to blood-borne pathogens. Understanding their prevalence, underlying causes and associated determinants is essential for implementing effective preventive measures in tertiary care institutions. Our objective is to assess the distribution, causes, and associated factors of NSIs among healthcare workers in tertiary care private setting in Peshawar.Methods: This retrospective descriptive cohort study involved 17 reported NSI incidents recorded in the Hospital Management Information System (HMIS) online complaint portal from September 2022 to September 2025. Data related to gender, profession, the cause of the injury, the condition of the patient and the hospital where the patient was hospitalized were coded and subjected to a descriptive analysis.Results: Most NSIs occurred among male healthcare workers (n=12, 70.6%), with nurses (n=8, 47.1%) and doctors (n=5, 29.4%) being the most affected professions. Catheter/line and syringe/line procedures were the leading causes of injury (35.3% each). The majority of exposures involved patients without documented blood-borne infections (76.5%), while hepatitis C and B were reported in 17.6% and 5.9% of cases, respectively. The Emergency Room (n=4, 23.5%) and pediatric ward (n=3, 17.6%) were the most common locations for NSIs. A significant association was observed between profession and injury cause (p = 0.027), with nurses predominantly affected by catheter- and syringe-related injuries. No significant associations were found between gender or hospital location and injury cause.ConclusionNeedle-stick injuries (NSIs) are a major occupational hazard, especially for nurses and during catheter/line or syringe procedures. These findings highlight the need for targeted training, strict safety protocol adherence, and robust reporting systems to protect healthcare workers. Results are preliminary, based on a single institution.